The Influence of Family Support on Students' Motivation and Achievement in English Language Learning - Moch Dheandra Al Reyva; Felix Yosafat Sitanggang; Khairun Nisa; Yunlis Y Banjarnahor; Sayra Nabila (Universitas Negeri Medan, 2025)
This study investigates the influence of family support on students' motivation and academic achievement in learning English. Using a quantitative correlational approach, data were collected from 27 seventh-grade students at SMPN 14 Medan through questionnaires measuring family support, learning motivation, and students' English scores. The results indicate a strong positive correlation (r = 0.697) between family support and students' English proficiency, highlighting emotional support as the most influential factor in fostering motivation. Instrumental and financial support also contributes to academic success, while excessive parental pressure may lead to stress and reduced engagement. These findings suggest that balanced family involvement is crucial in enhancing students' language learning experiences. Schools and policymakers should encourage parental engagement while also providing alternative support systems for students with limited family assistance to create a more inclusive and effective learning environment.